PENGARUH FINANCIAL LEVERAGE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lestari, Henny Setyo; Dewi, Rosiana (Manajemen Bisnis Kompetensi, 2016)
Purpose of this study is to analyze the influence of debt ratio, debt to equity ratio and interest coverage ratio to return on assets. The sample is used in this study the registered manufacturing companies in Stock Exchange Indonesia period 2009 to 2013. By using purposive sampling, the total of sample in this study is 106 manufacturing companies. This statistical method used multiple regression analysis that support by SPSS Versi 20. Independent variables in this study are debt ratio, debt to equity ratio and interest coverage ratio, whereas dependent variable is return on assets. Result of this study shows that debt ratio has negative and significant impact on return on assets, while debt to equity ratio and interest coverage ratio has positive significant impact on return on assets.Keywords: Debt ratio, debt to equity ratio, interest coverage ratio, return on assets